A descriptive overview of the interpreting service in Parliament - Lesch, Harold (Acta Academica: Critical views on society, culture and politics, 2010)
Language and language policy played a seminal role in the transformation of South Africa. The legislative framework laid down a multilingual language policy with the recognition of eleven official languages. Besides questions regarding its economic viability, there is a perception that the language policy is merely an attempt at political correctness. Nevertheless, societal issues and linguistic realities in the public arena necessitate that language service delivery in a multilingual country be granted a prominent role. This article portrays the reality of an interpreting service within the context of the public domain with specific reference to the highest state organs – nationally and provincially – as transformed entities, but also critically investigates the tasks to be fulfilled by language practitioners.